The Interaction of Substate Actors with the Global Public:: A Review of Aceh's Paradiplomacy through The Light of Aceh - Dermawan, Windy; Arrahman, Taufik; Alam, Gilang Nur; Primawanti, Henike (Faculty of Social and Political Sciences University of Bangka Belitung, 2024)
This article aims to explain the external persuasive actions of the Aceh Provincial Government in maintaining its Islamic identity through “The Light of Aceh” branding towards the global community. This action is referred to as paradiplomacy. As one of the subnational actors in Indonesia, Aceh Province is an area that has social and political dynamics from before independence to the present. Aceh has a distinctive identity and culture known as Serambi Mekah. Because of its efforts to maintain this identity, Aceh once fought for independence from Indonesia. Aceh's paradiplomacy certainly has different dynamics. However, the effort to maintain its identity has been a struggle from the past to the present. In the independence era, Aceh tried to fight for its identity with the struggle for independence, but in the post-independence era, Aceh fought for its regional interests through the framework of Regional Autonomy by establishing foreign relations and diplomacy to the global community. This research uses the theories of paradiplomacy and social identity to explain the persuasive actions taken by the Aceh Provincial Government through paradiplomacy to maintain its social identity. This research uses a qualitative method with data collection from interviews with relevant informants, documentation studies and internet-based studies. The results of this research show that the Aceh Provincial Government's paradiplomacy efforts to maintain its Islamic identity are carried out through branding “The Light of Aceh” by incorporating Islamic values in various components of the branding such as the main values of branding, logo philosophy, and branding commercial advertising videos. These values are socialised to the global community through various international activities by showcasing culture in dances, poems of clothing at international festivals, so that Aceh is better known by the global community with its Islamic identity.